Touch gesture interaction of preschool children towards games application using touch screen gadjet - Laili Farhana Md Ibharim,; Nadia Akma Ahmad Zaki,; Maizatul Hayati Mohamad Yatim, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study seeks to investigate the touch interaction of preschool children in using the touch screen gadget (iPad) for edutainment games application. This paper focuses on three objectives: (i) to identify the tauch interaction efficiency of preschool children in game application activities; (ii) to identify the level of touch screen gadgets interaction exposure among preschool children; (iii) to understand the tauch interaction experience of preschool children while playing the game using touch screen gadgets. A total of 20 preschool children from a kindergarten in Tanjong Malim involved as participants in this study. IPad representing touch screen gadget and four types of applications downloaded games for free were used for this study. The observation based on observation checklist was conducted by researchers assisted with 20 facilitators which roled as recorder and video recorder during the testing session. The results showed that (i) the tauch interaction of children against the games application using touch screen gadgets can be measured through their competence and experience in handling the iPad and gameplay; (ii) the level of children tauch interaction is good through interaction in way of iPad handling and gameplay using touch gesture; and (iii) tauch interaction experience of preschool children affect efficiency in understanding the concept of the game and touch screen handling.